On probation: an experimental analysis - Christoph Engel; Heike Hennig-Schmidt; Bernd Irlenbusch; Sebastian Kube (Max Planck Institute for Research on Collective Goods, 2009)
Does probation pay a double dividend? Society saves the cost of incarceration, and convicts preserve their liberty. But does probation also reduce the risk of recidivism? In a meta-study we show that the field evidence is inconclusive. Moreover it struggles with an identification problem: those put on probation are less likely to recidivate in the first place. We therefore complement the field evidence by a lab experiment that isolates the definitional feature of probation: the first sanction is conditional on being sanctioned again during the probation period. We find that probationers contribute less to a joint project; punishment cost is higher; efficiency is lower; inequity is higher. While experimental subjects are on probation, they increase their contributions to a joint project. However, once the probation period expires, they reduce their contributions. While in the aggregate these two effects almost cancel out, critically those not punished themselves do trust the institution less if punishment does not become effective immediately.
Keywords: C91; D03; H41; K14; K42; 330; probation; recidivism; public goods; punishment; experimental economics